Thermal noise effects on the magnetization switching of a ferromagnetic anomalous Josephson junction. (January 2021) - Guarcello, C.; Bergeret, F.S.
Abstract: We discuss the effects of thermal noise on the magnetic response of a lateral ferromagnetic Josephson junction with spin-orbit coupling and out-of-plane magnetization. The direction of the magnetic moment in the ferromagnetic layer can be inverted by using controlled current pulses. This phenomenon is due to the magnetoelectric effect that couples the flowing charge current and the magnetization of the ferromagnet. We investigate the magnetization reversal effect versus intrinsic parameters of the ferromagnet, such as the Gilbert damping and strength of the spin-orbit coupling. We estimate the magnetization reversing time and find the optimal values of the parameters for fast switching. With the aim of increasing the operation temperature we study the effects induced by thermal fluctuations on the averaged stationary magnetization, and find the conditions that make the system more robust against noise.